Teaching children movement concepts and skills - Werner, Peter ([S.l.] : Human Kinetics, 1993)
This video shows three condensed lessons that provide real-world examples of effectively teaching movement concepts and skills to children
Narrator: George Graham
Keywords: Physical education for children; Physical education and training; Teaching